2D Imaging Technique Electrical Impedance Distribution on Liquid with Paired Method and Using EIDORS Software - Ahmad Zarkasi; Abdurrouf Abdurrouf; Didik Rahadi Santoso (Natural B, Journal of Health and Environmental Sciences, 2017)
This paper discusses the 2D imaging technique of the electrical impedance distribution in the liquid by using the principles of Electrical Impedance Tomography (EIT).  A tomographic technique used in the imaging process is a adjacent or neighbor method, with input data obtained from measurements of the electrical potential at the boundary measuring object. Measurement data is reconstructed using open source software, i.e. EIDORS, which in image reconstruction using the principle of Finite Element Method (FEM). As a comparison on the results of image reconstruction by EIDORS, here used Boundary Data Simulation (BDS) were obtained from the same measurement data. Based on the results of the 2D images that have been obtained, it is evident that the techniques and imaging methods that have been used are able to show the distribution of electrical impedance value of the measuring object and have a good agreement with the results of BDS.